Improving Macroeconomics Problem-Solving Skill through Economics Learning Information System Media - Dewi Kusuma Wardani; Trisno Martono; Duta Sabiila Rusydi; Laurensia Claudia Pratomo; Dwi Hendra Kusuma (AL-ISHLAH: Jurnal Pendidikan, 2022)
The objective of this research was to develop an effective Economics learning information system media to improve students’ skill for Macroeconomics problem-solving. It used the research and development method. The Macroeconomics learning information system media was tested by using the quasi experimental research method with before –after design. It was conducted at the Study Program of Economics Education Program, Sebelas Maret University, Surakarta. Its population was 95 students. The findings of the N-Gain showed that the learning result of the experimental group was higher than that of the control group. The criteria of the N-Gain of the experimental group were high gain as much as 3.33%, moderate gain as much as 80% and low gain as much as 16.67%. Meanwhile, the control group did not have a high gain criterion or 0% but moderate gain as much as 46.67% and low gain as much as 53.33%. The score of the calculation on the questionnaire of problem-solving skill of the experimental group students who used the website-based information system media was higher than that of the control group students who did not use such media where the score percentage of the former was 80.61% while that of the latter was 72.18%. With such results, thus, this research was successful in developing a Macroeconomics learning information system media to improve student’s problem solving skill.